Organic crop management enhances Chicoric Acid content in lettuce - Rajashekar, C.B.; Oh, M.M.; Carey, E.E. (Scientific Research Publishing, Inc., 2012)
L- chicoric acid is a dominant phenolic compound in lettuce (Lactuca sativa L.) and has been shown to accumulate in response to many abiotic stresses and crop management practices. It is a potent inhibitor of human immunodeficiency virus (HIV-1) integrase needed for the replication of this virus and for the productive infection of the host cell. L- chicoric acid has been found to act synergistically in combination with anti-HIV drugs used for treating acquired immuno-deficiency disorder (AIDS). We show in this study that organic management practices increase the chicoric acid content by nearly 2-fold compared to conventional management practices while they did not have a significant effect on the overall accumulation of phenolic compounds and antioxidants. Similar increase was observed in quercetin-3-O-glucoside under organic management. In addition, pre-plant fertilization decreased the levels of many phenolic compounds including chicoric acid under organic management unlike under conventional management. However, organically managed crop without pre-plant fertilization had better growth and produced about 2.5 times higher yield and higher chicoric acid content than did the conventionally managed crop. Thus, the results show that long term organic crop management practices, but avoiding pre-plant fertilization, can significantly enhance the yield of antiretroviral agent chicoric acid in lettuce.